2006
DOI: 10.1179/174328206x105416
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal growth and dynamics of epixylic bryophytes in Bohemian old-growth forest

Abstract: Seasonal patterns in growth and dynamics of 13 epixylic bryophyte species (six liverworts and seven mosses) were studied within permanent plots in the Ž ofínský prales old-growth forest in south-eastern Bohemia, Czech Republic. Transparencies were used to record positions and cover of bryophyte colonies within each plot twice a year (in spring and autumn) for periods of 1-4 years. Percentage growth of species populations and growth dynamics of their colonies were analysed in order to identify seasonality in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, a direct or indirect effect of climatic drivers cannot be ruled out, and the strong relationship between the first ordination axis and snow cover and elevation is intriguing. In a study from the Czech Republic, Jansová () found that growth and local extinction dynamics of bryophyte communities on beech logs were more intensive in the winter than in the summer. This suggests that the length of the snow free period in winter may be an important factor structuring epixylic communities, just as it has been shown for ground‐living bryophytes in alpine snow‐beds (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…However, a direct or indirect effect of climatic drivers cannot be ruled out, and the strong relationship between the first ordination axis and snow cover and elevation is intriguing. In a study from the Czech Republic, Jansová () found that growth and local extinction dynamics of bryophyte communities on beech logs were more intensive in the winter than in the summer. This suggests that the length of the snow free period in winter may be an important factor structuring epixylic communities, just as it has been shown for ground‐living bryophytes in alpine snow‐beds (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…In the temperate forest zone, microclimate changes significantly during the season and so do the dynamics of bryophyte growth. Generally, authors agree that the most important period for annual growth is autumn (Tamm, 1953; Pitkin, 1975), though others report the highest growth rates in late winter and early spring (Jansová, 2006; Rincon and Grime, 2009). In the temperate zone — and especially in mountainous regions — both these periods are characterized by very stable low temperatures and the high atmospheric humidity associated with frequent precipitation, which is crucial for poikilohydric bryophytes.…”
Section: Introductionmentioning
confidence: 99%